Quality assurance in islamic educational institutions: Integrating religious values with global accreditation frameworks - Hamdanah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study examines how Islamic educational institutions can integrate religious values with global accreditation frameworks in order to strengthen their quality assurance systems. Drawing on qualitative analysis of policy documents, institutional reports, and expert perspectives, the research explores the ways in which international quality standards—such as governance structures, curriculum coherence, documentation systems, and continuous evaluation—can be aligned with the ethical and pedagogical traditions that characterise Islamic education. The findings reveal that many institutions are in a transitional phase: increasingly engaged with global benchmarks yet still negotiating how to articulate faith based commitments within technical accreditation instruments. Successful institutions tend to translate religious values into operational indicators, including managerial integrity, professional conduct among teachers, and a sustained culture of accountability. The study also identifies capacity building and leadership character as decisive factors in determining whether integration becomes substantive or merely symbolic. Ultimately, the research argues that combining global frameworks with religious values is not a competing agenda but a strategic and cultural necessity for Islamic educational institutions in the twenty first century. This integration allows institutions to enhance their credibility in international arenas while safeguarding their distinctive intellectual and spiritual heritag